ANALISIS PENILAIAN RESIKO TERHAHAP EVALUASI RENCANA PASCATAMBANG BATUBARA MENGGUNAKAN SKALA LIKERT - Shilvyanora Aprilia Rande; R. Andy Erwin Wijaya (PROMINE, 2014)
Mining business activities must be implemented by taking into account the principle of the living environmnet transparency, and public participation. In order to create sustainable development, the activity of mining if it is Research is done at a coal mine, and the district tabalong balangan district, south kalimantan. The results of risk assessment obtained program that has the potential negative impact of three of which is handling of the remaining fuel oil obtained score 39, a lubricant, as well as chemical the recovery of land contaminated chemical, oil, and yet obtained score 39 and monitoring of surface water and ground water obtained score 39. The aspect of the sustainability of high that is the economic aspect and social, if applied to the plan of construction is highly supportive of the map. The aspect of environmental the possibility of small Sustainable this needs to handling, the management and monitoring so that between a map extension of reclamation and post-mine plan can support each other.